2013
DOI: 10.1016/j.jpainsymman.2012.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Control of Refractory Hemorrhagic Radiation Proctitis With Ozone Therapy

Abstract: Persistent advanced HRP was significantly improved with O3T. The addition of O3T can be useful as a complementary treatment in the long-term management of HRP and, as such, merits further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…29,[34][35][36][37][38][39] For example, ozone has been employed as a powerful drinking-water disinfectant and oxidant. 34,35,40 On the other hand, when the ozone level in an atmosphere exceeds a certain threshold value, the exposure to this gas becomes hazardous to human health and can cause serious health problems (e.g.…”
Section: -28mentioning
confidence: 99%
“…29,[34][35][36][37][38][39] For example, ozone has been employed as a powerful drinking-water disinfectant and oxidant. 34,35,40 On the other hand, when the ozone level in an atmosphere exceeds a certain threshold value, the exposure to this gas becomes hazardous to human health and can cause serious health problems (e.g.…”
Section: -28mentioning
confidence: 99%
“…However, data on the use of ozone or ozonated oils in radiation proctitis are limited. Recently, Clavo et al (26) reported the beneficial effects of ozone therapy on refractory haemorrhagic radiation proctitis. In the study, 17 patients received an ozone gas mixture via rectal insufflations and topical application of ozonised oil, and were followed up for a median of 40 months (3-56 months).…”
Section: Discussionmentioning
confidence: 99%
“…In the study, 17 patients received an ozone gas mixture via rectal insufflations and topical application of ozonised oil, and were followed up for a median of 40 months (3-56 months). Clavo et al (26) concluded that ozone treatment improved the clinical symptoms of haemorrhagic radiation proctitis. However, this is the only study published in the English- language literature, and to date, no studies have reported the effects of OzOO on histopathological findings of ARP in animals or in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozone (O 3 ) is an oxidizing gas which exhibits industrial applications such as drinking-water treatment, microelectronic cleaning processes, among others (Glaze 1987;Patil et al 2009;Bocci et al 2011;Korotcenkov and Cho 2012;Clavo et al 2013;Graham et al 2013;Simoes and Simoes 2013). The real-time monitoring of the O 3 concentration levels is essential for human health.…”
Section: Introductionmentioning
confidence: 99%